A pilot study of escape, avoidance, and approach behaviors in treated alcohol-dependent males. Issue 6 (3rd July 2019) - Sheynin, Jony; Myers, Catherine E.; Ghafar, Farahnaz; Morris, Alejandro N.; Morley, Kirsten C.; Haber, Paul S.; Moustafa, Ahmed A.
ABSTRACT: Alcohol-dependent individuals are often reported to use behavioral strategies both to escape from and avoid negative affective states, and also to approach positive affective states. However, there has been little examination of how these individuals acquire and express these types of behaviors. In this study, male adults meeting the International Classification of Diseases–10th Revision (ICD–10) criteria for alcohol dependence recruited from an outpatient treatment clinic and healthy male controls were given a computer-based task to assess learning and performance of escape, avoidance, and approach behaviors. In this task, participants control a spaceship and can either gain points by shooting an enemy spaceship or hide in safe areas to escape or avoid on-screen aversive events. We found that patients with alcohol dependence exhibited greater escape and approach behaviors, tended to show greater avoidance behavior, and achieved higher total score on the computer task than healthy controls. This is the first demonstration of such behavioral differences in this population, supporting the overactivation of both positive and negative reinforcement systems in alcohol dependence, and suggesting that such behavioral biases are not limited to alcohol-related cues. The contribution of this work to behavioral assessment and therapeutic approaches, as well as possible future directions, are discussed.